+0  
 
+5
326
1
avatar

y=_x+_ with the points of (3,-2) and(6,4) using point slope form

Guest Jul 13, 2015

Best Answer 

 #1
avatar+17744 
+5

The point-slope form is:  y - y1 = m(x - x1)

where the point is (x1, y1) and the slope is m.  m  =  (y2 - y1) / (x2 - x1)

For this problem:  x1 = 3, y1 = -2, x2 = 6, and y2 = 4.

Therefore:  m  =  (4 - -2) / (6 - 3)  =  6/3  =  2

The equation is:  y - -2  =  2(x - 3)     --->     y + 2  =  2x - 6     --->     y  = 2x - 8

geno3141  Jul 13, 2015
 #1
avatar+17744 
+5
Best Answer

The point-slope form is:  y - y1 = m(x - x1)

where the point is (x1, y1) and the slope is m.  m  =  (y2 - y1) / (x2 - x1)

For this problem:  x1 = 3, y1 = -2, x2 = 6, and y2 = 4.

Therefore:  m  =  (4 - -2) / (6 - 3)  =  6/3  =  2

The equation is:  y - -2  =  2(x - 3)     --->     y + 2  =  2x - 6     --->     y  = 2x - 8

geno3141  Jul 13, 2015

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.